Horizontalism and Wisdom Dialogues to Build Trust: A Case Study of Collaborations With Immigrant Farmers in Minnesota - Wauters, Vivian M.; Hoidal, Natalie (Frontiers in Sustainable Food Systems, 2022)
Collaboration between farmers and other farm support professionals is a critical tool for food systems transformation. Collaborative research and outreach can address structural inequalities that limit the success of immigrant and minority growers and uplift farmer knowledge, which has been systemically valued below that of academic knowledge. Agroecologists who work at the synthesis of science, movement, and practice propose wisdom dialogues and horizontalism as principles by which to develop collaborations that avoid reinforcing structural inequalities due to race, gender, and traditions of valuing academic knowledge above that of farmers. Public entities, such as land grant universities and state agencies, have a particular responsibility to address structural inequalities and serve the diversity of farmers in their region. This study examines the use of collaborative learning processes, such as wisdom dialogues and horizontalism, by public and non-profit professionals in their collaborations with a group of immigrant farmers in the Upper Midwest. We used a qualitative interview approach with two farmers, two of their advisers, and eight of their collaborators at the University of Minnesota Extension, Department of Agriculture, and a local agricultural non-profit. Through the interviews we examined each of their perspectives on current and potential collaborations by discussing the motivations, resources, and effects for and of collaboration between immigrant farmers and farm support professionals. Farmer interviewees emphasized that collaborations between immigrant and non-immigrant individuals and groups must develop with non-exploitative motivations and preparation undertaken by non-immigrant individuals to better understand the experience of immigrant farmer prior to engaging in collaboration. Emergent themes from interviews with non-farmers included a strong commitment to providing access to knowledge and resources, and recognition that collaboration improved the ability to accomplish institutional goals, indicating use of wisdom dialogues and horizontal learning at varying levels within current work. Interviewees emphasized that institutional support was an important determinant for how much they could prioritize relationships and collaboration in their work. Based on interviewees' experiences, support and continued opportunities for learning are critical to facilitate continued use of wisdom dialogues and horizontalism to address different conceptions of equity and equality, and for developing intentional and mutually beneficial collaborations.